A AMEAÇA SIMBÓLICA DAS COTAS RACIAIS NA MÍDIA BRASILEIRA: o negro nas telenovelas - GOMES, Igor Bergamo Anjos (2008)
The Brazilian soap opera was consecrated as a media product and culture compound and resultant of particularities of the it historizes of the country and of the own development of television. The history of the insert blacks in the Brazilian soap opera allows to conclude that the pamphlets don't portray the population of the country, that is composed for the most part by mestizos and black. The proposal of the present rehearses dissertation it is to analyze the debate around the proposition of the quotas in soap opera, it discusses that has as social actors, Senator Paulo Paim, author of the project of quotas, the soap operas authors, and CIDAN (I Center Brazilian of Information and documentation of the Black Artist), problematizing concerning the reactions and consequences of the adensament of that debate, that makes interface with the problem related to the insert of blacks in soap opera, that historically camouflaged the black under the myth of the mestizos people, as a whiting strategy.